2009
DOI: 10.2169/internalmedicine.48.1308
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Meropenem for the Treatment of Aspiration Pneumonia in Elderly Patients

Abstract: Objective and Background In Japan, an increase in the elderly population is associated with an increased incidence of aspiration pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…It is usually caused by bacteria, sometimes polymicrobial, especially in patients who are at risk for aspiration [9, 10]. The majority of postoperative pneumonia cases are caused by gram-negative, aerobic bacteria including Pseudomonas , Klebsiella , and Enterobacter species, among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually caused by bacteria, sometimes polymicrobial, especially in patients who are at risk for aspiration [9, 10]. The majority of postoperative pneumonia cases are caused by gram-negative, aerobic bacteria including Pseudomonas , Klebsiella , and Enterobacter species, among others.…”
Section: Introductionmentioning
confidence: 99%
“…20 The bacteriology in this study was similar to that in recent studies, showing that aerobes as pathogen of aspiration pneumonia play a more important role than anaerobes. 21,22 Several limitations of our study should be explained. This study was retrospective, making our findings vulnerable to commonly discussed biases and confounding factors, although this is the largest study of data collected from the prospective carbon monoxide poisoning registry.…”
Section: Discussionmentioning
confidence: 94%
“…Yamamoto et al reported that MEPM at 1.5 g daily showed an efficacy rate of 74.2% (23/31) in NHCAP patients, and the efficacy rate of tazobactam/piperacillin was slightly higher (22/29, 87.9%) [18]. In addition, the efficacy rate of MEPM at 1 g daily in elderly patients with aspiration pneumonia was reported to be 61.3% [19]. We were able to evaluate the plasma concentration of MEPM in one patient with empyema whose MEPM dose was increased from 1.5 g to 3.0 g/day because of insufficient clinical efficacy, and this patient showed an increased plasma level of MEPM from 15.2 mg/ml to 41.0 mg/ml at one hour after MEPM administration.…”
Section: Discussionmentioning
confidence: 99%